The Traditional Circus of the State of Rio de Janeiro, between the Tactics and the Improvisations - Sluchem Tavares Cherem (Revista Brasileira de Estudos da Presença)
It is a paper that discusses the current scenery of the Traditional Circus in the state of Rio de Janeiro, analyzing the tactics and improvisations witch the actors use as forms of survival and resistance. The investigation is based on data collected in artistic class meetings, interviews, press materials and specialized bibliography. An introduction is presented that outlines the methodology and presents a brief concept of Traditional Circus and its contemporary characteristics in that state. Next, the strategies adopted by circus performers to preserve tradition and artistic language are detailed. It is concluded that many of the characteristic elements of Traditional Circus are consequences of tactics developed by artists as a form of survival.